PENGARUH KARAKTERISTIK PERSONALITAS TERHADAP HUBUNGAN ANTARA KONTAK DENGAN ORANG LOKAL DAN PENYESUAIAN LINTAS BUDAYA - Tuty Herlina (Media Riset Bisnis & Manajemen, 2004)
Cross cultural adjustment is becoming a great concern for multinational and international companies in running their business overseas. It concerns with the prfomance and the completion of overseas assginment of expatriates. The goals of the research are to provide a better understanding on the impactof host national contact towards cross cultural adjustment and also on how interaction process within hostnational swicth provide cross cultural adjust- ment Personal characteristics considered as a major factor play significant contribution toward the relationship between host national contact and cross cultural adjustment.